Media Pembelajaran Digital Berbasis Scratch sebagai Inovasi Pembelajaran di TK Gracia Waharia Nabire - Kristia Yuliawan; Wisna Bara’ Padalingan (Jurnal Teknik Informatika dan Teknologi Informasi, 2025)
This research aims to develop a Scratch-based digital learning media called Rimba Ceria, intended for early childhood at Gracia Waharia Kindergarten, Nabire, Papua. The background of this activity departs from the limited educational resources and the low involvement of children in the learning process in the 3T (disadvantaged, frontier, and outermost) areas. Rimba Ceria media is designed in an interactive and interesting manner, in accordance with the characteristics of early childhood learning which are visual and game-based. The development process uses the ADDIE model approach which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The results of the development show that this medium successfully integrates text, audio, video, and interactive elements to introduce the categories of terrestrial, marine, and aerial animals. This innovation not only fills the gap in relevant learning media in remote areas, but also contributes to improved computational thinking, problem-solving skills, creativity, and early childhood learning engagement. Evaluation shows that this media is well received by students and teachers, and has the potential to be replicated in similar areas. Thus, Rimba Ceria is an adaptive and applicative educational solution in supporting the equitable distribution of the quality of early childhood education, especially in areas with limited access to technology and learning resources.